Optimasi Sumber Daya Pada Usaha Berskala Kecil Di Tengah Masa Pandemi Menggunakan Metode Simpleks - Matheus Supriyanto Rumetna; Tirsa Ninia Lina; Paulus Burdam; Jeance Yulanda; Danu Saputro; Wahyu Putra Bahari; Aprinando Sianturi; Richard Riupassa; Nomensen Dautot; Yuan Leky; Greito Sahetapy; Indri Indri; Brian Ackly Tobelo (PETIR, 2022)
As developments in the industrial sector move forward, there is more and more competition, but now there is one major barrier, namely the Covid-19 pandemic. This pandemic has forced the government to implement Large-Scale Social Restrictions and the Enforcement of Restrictions on Community Activities. This has a negative impact on one of the small-scale businesses, namely Ibu Olan's home-based business because there is a decline in people's purchasing power which has an impact on the profit of Ibu Olan's business which is also reduced. This problem experienced by Ibu Olan has become a dynamic that is also felt by other small-scale businesses. In order for this business to continue to survive in the midst of the Covid-19 pandemic storm, it can use one of the methods contained in the Linear Program, namely the Simplex method. The main objective of this research is to help small-scale businesses in terms of resource optimization. As a result, Ibu Olan's home-based business earns a profit of IDR 90,000,- per day from the sales of Sampoerna and Surya cigarettes. These results are used as a reference or benchmark for small businesses in terms of making decisions for business development and the main guarantee is that this method provides the best solution for problem solving.